ChemInform Abstract: Li17Sb13S28: A New Lithium Ion Conductor and Addition to the Phase Diagram Li2S—Sb2S3. Issue 50 (December 2015) - Huber, Sebastian; Pfitzner, Arno
Abstract: Li17 Sb13 S28 is prepared by solid‐state reaction of stoichiometric amounts of anhydrous Li2 S and Sb2 S3 (graphitized evacuated silica tubes, 773 K, 5 weeks).